2023
DOI: 10.1029/2023ja031690
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Flow Vortex Induced by the Sudden Decrease in the Solar Wind Dynamic Pressure

Yaqi Jin,
Jøran Idar Moen,
Andres Spicher
et al.

Abstract: Abrupt changes in the solar wind dynamic pressure can greatly affect the Earth's magnetosphere‐ionosphere system. We present an ionospheric flow vortex in the morning sector during the sudden decrease in the solar wind dynamic pressure. The flow vortex was clearly observed by both the Hankasalmi radar and the azimuthal scan mode of the European Incoherent Scatter (EISCAT) Svalbard Radar (ESR). The flow vortex was first seen in the eastern field of view (FOV) of the Hankasalmi radar, and then propagated polewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This encounter time is close to the onset of the negative B total ( E a ) impulse in Figure 3 (09:00 UT). Previous studies have reported flow vortices caused by the decrease of solar wind dynamic pressure (e.g., Hori et al., 2012; H. Y. Zhao et al., 2016; Jin et al., 2023). We propose the transient detected by ARTEMIS‐P2 is possible to induce the observed vortex and impulses.…”
Section: Resultsmentioning
confidence: 99%
“…This encounter time is close to the onset of the negative B total ( E a ) impulse in Figure 3 (09:00 UT). Previous studies have reported flow vortices caused by the decrease of solar wind dynamic pressure (e.g., Hori et al., 2012; H. Y. Zhao et al., 2016; Jin et al., 2023). We propose the transient detected by ARTEMIS‐P2 is possible to induce the observed vortex and impulses.…”
Section: Resultsmentioning
confidence: 99%